Workload, Knowledge Sharing, and Teamwork on Lecturer Productivity at Strada Indonesia University - Sholichudin; Anggi Tiur Maduma; Joko Prasetyio; Indasah; Ratna Wardani (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2025)
This study aims to analyze the influence of workload, knowledge sharing, and teamwork on the productivity of lecturers at Strada Indonesia University. The research method used a quantitative approach. Data were collected through questionnaires distributed to staff at Strada Indonesia University and analyzed using dummy linear regression analysis techniques to identify the relationship between these variables and productivity. The results showed that high workloads had a negative impact on productivity, while knowledge sharing and teamwork had a significant positive influence. Effective knowledge sharing and good teamwork can increase productivity by facilitating the flow of information, improving skills, and strengthening working relationships between individuals.